2015
DOI: 10.1259/bjr.20150586
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study comparing radiographer- and clinician-based localization for patients with metastatic spinal cord compression (MSCC) to assess the feasibility of a radiographer-led service

Abstract: prospective study comparing radiographer-and clinician-based localization for patients with metastatic spinal cord compression (MSCC) to assess the feasibility of a radiographer-led service. Br J Radiol 2015; 88: 20150586. FULL PAPERA prospective study comparing radiographer-and clinicianbased localization for patients with metastatic spinal cord compression (MSCC) to assess the feasibility of a radiographer-led service Objective: To investigate whether there was parity between treatment fields localized by ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…From this, it may be suggested that radiographer-led roles have the potential to improve access to palliative radiotherapy through reduced waiting times. 26,27 Statistical analyses in both studies show a high correlation between radiographer's and clinical oncologist's plans, supporting the authors' claim of equivalence in work quality. Their conclusion that radiographer-led pathways can reduce waiting times is, however, a supposition.…”
Section: Discussionsupporting
confidence: 58%
“…From this, it may be suggested that radiographer-led roles have the potential to improve access to palliative radiotherapy through reduced waiting times. 26,27 Statistical analyses in both studies show a high correlation between radiographer's and clinical oncologist's plans, supporting the authors' claim of equivalence in work quality. Their conclusion that radiographer-led pathways can reduce waiting times is, however, a supposition.…”
Section: Discussionsupporting
confidence: 58%